TonB-Dependent Heme Iron Acquisition in the Tsetse Fly Symbiont Sodalis glossinidius - Hrusa, Gili (Appl Environ Microbiol, 2015)
Sodalis glossinidius is an intra- and extracellular symbiont of the tsetse fly (Glossina sp.), which feeds exclusively on vertebrate blood. S. glossinidius resides in a wide variety of tsetse tissues and may encounter environments that differ dramatically in iron content. The Sodalis chromosome encodes a putative TonB-dependent outer membrane heme transporter (HemR) and a putative periplasmic/inner membrane ABC heme permease system (HemTUV). Because these gene products mediate iron acquisition processes by other enteric bacteria, we characterized their regulation and physiological role in the Sodalis/tsetse system. Our results show that the hemR and tonB genes are expressed by S. glossinidius in the tsetse fly. Furthermore, transcription of hemR in Sodalis is repressed in a high-iron environment by the iron-responsive transcriptional regulator Fur. Expression of the S. glossinidius hemR and hemTUV genes in an Escherichia coli strain unable to use heme as an iron source stimulated growth in the presence of heme or hemoglobin as the sole iron source. This stimulation was dependent on the presence of either the E. coli or Sodalis tonB gene. Sodalis tonB and hemR mutant strains were defective in their ability to colonize the gut of tsetse flies that lacked endogenous symbionts, while wild-type S. glossinidius proliferated in this same environment. Finally, we show that the Sodalis HemR protein is localized to the bacterial membrane and appears to bind hemin. Collectively, this study provides strong evidence that TonB-dependent, HemR-mediated iron acquisition is important for the maintenance of symbiont homeostasis in the tsetse fly, and it provides evidence for the expression of bacterial high-affinity iron acquisition genes in insect symbionts.